PROSES ADAPTASI (EKRANISASI) NOVEL “TENGGELAMNYA KAPAL VAN DER WIJCK” KARYA HAMKA - Rizki, Dwindica (Institut Seni Budaya Indonesia Bandung, 2017)
Film is an audio visual communication media to convey a message to apresiator/ audience who watch it. Drama is one of the films that have a particular plot and theme, such as; romance, social life, culture, history of struggle, and others. In the Movie of “Tenggelamnya Kapal Van Der Wijck” directed by Sunil Soraya and adapted from the novel by Hamka, tells of a young Minangkabau who can not marry the girl he loves because they have different social backgrounds. The problem is described by Zainuddin as the main character who can not marry Hayati. Minangkabau or abbreviated Minang refers to the cultural and geographical entities characterized by the use of Minang language, customs that embrace the matrilineal kinship system, and a strong Islamic identity. Matrilineal is one of the main aspects in defining the identity of Minang society. The sociological approach was used to obtain a description of Hamka's novel adaptation into the film “Tenggelamnya Kapal Van Der Wijck”. This paper shows how the process of ecranization or adaptation can describe the storyline, characters and characterizations, as well as the background of Minang cultural hegemony in the complexity of the events attached to the characters in the film “Tenggelamnya Kapal Van Der Wijck”.